Values in General Education School: Teachers’ Approach - Martišauskienė, Elvyda; Vaičekauskienė, Snieguolė (Pedagogika, 2015)
Moral values are characterized as meaning of human life and plenitude condition. The basis of moral values are always spiritual and ensuring human as individual united becoming. The influence of moral values to better pupil achievements and thinking are based on academic research. Attention is drawn, that values of educators are related not only with their own work but also with ability to create more humane relations and educational process – to work with all age group students and base communication in educational process on self-esteem and creativity. The values of educators have an influence on student maturity – education based on moral values determine positive social behavior, allows the better understanding of behaviour impact on yourself and others, develop his ethic vocabulary. The research discovers that in modern school moral values are not frequent – they formed a quarter of all identified values. Values can be considered as aspect of organization of educational process, school management and work with parents. However by this way the attitude is expressed to school management and education based on humane relations, establishment of conditions is emphasized to correspond not only the need of educator but also the needs of other schools community members. Discussing values, educators often express problems arising while organizing educational process. So it must be assumed that various pedagogical difficulties have influence on value education – giving a sense to student activities require considerable amount of effort. Therefore short-term goals are set and pupil moral position is understood in school. Little attention to spiritual learning perspectives.